Delayed occupational asthma from epoxy exposure. - Brock,Jacobsen I; Baelum,J; Carstensen,O; Skadhauge,LR; Feary,J; Cullinan,P; Sherson,DL (Occup Med (Lond), 2019)
BACKGROUND: A delayed asthma reaction occurring several hours after exposure is difficult to diagnose. AIMS: To confirm a delayed asthma reaction in five workers following epoxy exposure. CASE REPORT: Working conditions with exposure to epoxy encountered at the workplace were reproduced in a challenge chamber. Specific inhalation challenge (SIC) with epoxy was compared to a control challenge. All five cases had delayed a asthma response 6-15 h after epoxy exposure. CONCLUSIONS: Our study confirms that SIC is a useful tool in diagnosing delayed asthma response.